Neonatal mortality rates and association with antenatal corticosteroids at Kamuzu Central Hospital. (December 2020) - Valentine, Gregory C.; Chiume, Msandeni; Hagan, Joseph; Kazembe, Peter; Aagaard, Kjersti M.; Patil, Monika
Abstract: Objective: Malawi has one of the highest child mortality rates in the world, and neonates account for nearly half of all under-five mortality. No previous study has reported neonatal outcomes in Malawi over 12 months. We aimed to evaluate outcomes in the neonatal intensive care unit (NICU) at Kamuzu Central Hospital (KCH) and to determine if there was an association between increased survival and antenatal corticosteroid (ACS) exposure. Study design: We introduced a prospective, observational electronic database to collect 122 de-identified variables related to neonatal outcomes for all neonates admitted to the KCH NICU over 12 months. Patients with congenital anomalies were excluded. We compared neonatal mortality rates in neonates who were exposed to ACS compared to those who were not. Statistical methodology included the Wilcoxon rank sum test, Fisher's exact test, and logistic regression. Results: Of 2051 neonates admitted to the KCH NICU, the overall neonatal mortality rate was 23.1% and remained similar across 12 months. Mortality was inversely related to birth weight, and outborn neonates referred to KCH had the highest mortality rate (29%). After controlling for confounding covariates, inborn infants exposed to ACS had significantly lower odds of death compared to those without exposure to ACS (adjusted odds ratio = 0.46, 95% confidence interval: 0.24–0.88, p = 0.020). Conclusion: Lower birth weight, outborn, and no ACS exposure were associated with increased mortality. ACS was associated with a 54% reduction in odds of mortality in inborn neonates highlighting the need for further evaluations of ACS use in resource-limited settings. Highlights: This is the largest and longest-run study evaluating neonatal outcomes in Malawi. Overall mortality of all neonates was 23.1% from October 2017–October 2018. 61% of neonates who suffered mortality did so within the first 72 h of life. Lack of antenatal corticosteroid exposure was associated with increased mortality.